Heat transfer in solid halogenated methanes: trifluoromethane - Konstantinov, V.A.; Revyakin, V.P.; Sagan, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The isochoric thermal conductivity of solid trifluoromethane was investigated for three samples of different densities in the interval from 75 K to the onset of melting. The isochoric thermal conductivity first decreases with increasing temperature, passes through a minimum at T 100 K, and then starts to increase slowly. The results obtained are compared with the thermal conductivities of other freons of methane series. The correlation between the temperature dependence of isochoric thermal conductivity and the character of the rotational molecular motion is discussed.